Clinical effect evaluation of the application of Er:YAG laser to peri-implantitis - LI Feng-zhou; XUE Fan (口腔疾病防治, 2016)
Objective To compare the effectiveness of an Er:YAG laser and mechanical debridement for the treatment of peri-implantitis. Methods 22 cases of peri-implantitis patients were divided into 2 groups according to the single blind randomized control principle. The experimental group was treated by Er:YAG laser irradiation, the laser energy was set to 100 mJ/pulse, frequency of 10 Hz; plastic curette and 0.2% chlorhexidine antimicrobial therapy was used in the control group. Clinical periodontal index test including plaque index, bleeding index, probing depth and clinical attachment level was conducted at baseline, 3 months and 6 months. Results At baseline, the difference of clinical periodontal index between the experimental group and the control group had no statistical significance (P>0.05). After 3 months of treatment (P<0.01) and 6 months (P<0.05), bleeding index, plaque index of test group and control group had significant difference. Probing depth was reduced by 3 and 6 months after treatment in both 2 groups, and the probing depth had significant difference (P<0.05); while clinical attachment level value showed no statistical significance between the two groups (P>0.05). Conclusion The research shows that the Er:YAG laser treatment can significantly improve peri implant inflammation level, effectiveness of peri-implantitis control is superior than the mechanical curettage treatment.